The Role of Reflection in Doctoral Education: An Integrative Review of Approaches to Supporting Well-Being and Developmental Growth - Kamilla Klefbeck (Education Sciences)
Doctoral supervision is a complex and multifaceted endeavor that requires balancing the dual objectives of promoting academic development and supporting the well-being of doctoral candidates. This study examines how care-focused strategies and the concept of professional uncertainty can guide supervisors in addressing these demands. An integrative review methodology was used to synthesize findings from educational, psychological, and health-related literature, identifying methods and practices that enhance well-being and personal growth among doctoral candidates. Results indicate that fostering supportive relationships, integrating coaching practices, and adopting salutogenic approaches promote resilience and autonomy in doctoral students. Supervisors’ self-care and collegial support were also highlighted as critical for sustaining their capacity to guide students successfully. Challenges include managing conflicting expectations, navigating cultural diversity, and addressing stress within supervisory relationships. By emphasizing relational and ethical dimensions, the study demonstrates how reflective supervision can create environments that support both academic progress and mental health. While focused on doctoral education, these findings may also offer insights for teacher education programs, suggesting ways in which principles of care, reflection, and professional uncertainty could be relevant in broader educational contexts. Recommendations for practice include adopting structured supervision cycles and embedding care as a core principle in institutional policies. This paper offers practical insights and tools for integrating care-based strategies into doctoral supervision, providing a framework to enhance doctoral students’ well-being and adaptability while helping supervisors balance their dual roles.